Throwing velocity differences in training vs. European championships in the water polo Spanish female national team - Alcaraz, P.; Ferragut, C.; Abraldes, A.; Vila, H.; Argudo, F.; Rodriguez, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The velocity component of accurate, overhead water polo throws, especially in the act of goal shooting, is an important ingredient of successful scoring ability. It seems that when a tactical situation (goalkeeper) is included the speed has been smaller. However, there are no studies that presents if differences are found in performance between training or real play situations. PURPOSE: To compare the throwing velocity differences in training vs. European championships in the Water Polo Spanish female national team. METHODS: Eleven healthy woman sub-champions of Europe (22.5 ± 2.9 years; 65.0 ± 8.0 kg; 171.7 ± 7.5 cm) were tested at training (precompetitive period), or at the Europe Championships (competitive period), always in a indoor swimming pool. For the training test, a radar, placed ten meters behind the goal, and aligned with the penalty line, registered two throwing at maximum intensity from the penalty line. The shooting was carried out with a goalkeeper. The best shot was selected for the analysis. For the championships test, the same position of the radar was allowed. We analyzed all the shots carried out from the penalty line in the last five matches. T-test for dependent samples was used (P </= 0.05). RESULTS: There were no between-situations differences. The data confirm that the throwing velocity was similar in the training situation (15.46 ± 1.15 m•s-1), when they were compared to the championship condition (15.55 ± 2.24 m•s-1). CONCLUSION: The throwing velocity is similar when a water polo player performs a shot from the penalty line with goalkeeper, independently the situation: training vs. international championship. In this sense, the control of the throwing velocity over the training can be a very reliable method of the championships shots velocities.